Knowledge, Attitude, Practices of Health and Social Care Professionals on Dementia Care in a Tertiary Care Hospital, Bangladesh (Sir Salimullah Medical College Journal, 2025)
Background: Dementia is perceived as one of the leading public health concerns and social care challenges of the 21st century. However, accessing appropriate healthcare and social support for people with dementia and their family members is difficult in Bangladesh and there are growing calls for skilled and experienced health and social care professionals in dementia care.  The present study is an endeavor to explore the knowledge, attitude, and practices of dementia care among health and social care professionals in Bangladesh. Methods:  A cross-sectional research design was conducted to investigate the existing knowledge, attitudes, and practices about dementia care among health and social care professionals (N=99) in a tertiary care hospital in Bangladesh where many doctors, nurses and psychologists are working and getting training every year. The Alzheimer's Disease Knowledge Scale (ADKS) and a self-designed structured questionnaire on attitudes and practices were used. Results: The overall mean score of health and social care professionals' dementia knowledge was 19.09 (SD = 3.90) out of 30 (63.87%). Items related to "life impact" were answered best, while those related to "care giving" were the lowest. The study revealed that 93.9% of professionals believe that much can be done to improve the quality of life of caregivers of people with dementia, and 67.7% do not feel uncomfortable being around people with dementia. However, it also found that 21.2% of professionals have no experience dealing with dementia patients. Most of the participants (69.7%) agreed to provide psychological support to caregivers of dementia patients. However, 15.2% of participants do not recommend sources of social support available to caregivers if needed.  Conclusion: The study concluded that there is a need for attention to policy recommendations aimed at enhancing the knowledge, attitudes, and practices of dementia care among health and social care professionals in Bangladesh.Sir Salimullah Med Coll J 2024; 32: 16-22